(untitled) (Homoeopathy for All, 2021)
Sinuses are air filled spaces in the skull that communicate with the nose, situated within the bones between eyes, behind cheekbones, and in forehead. They make mucus, which keeps the inside of nose moist. Sinusitis is a condition in which the cavities around the nasal passages become inflamed. An infection in the nose and upper respiratory tract can spread to the sinuses. Sinuses can get acutely infected during an episode of cold or many times they remain chronically infected due to repeated colds or non clearance of infection. This article provides an overview of the aetiology, diagnosis, and appropriate general & homoeopathic management of this disorder.